Pengolahan Data Buah Menggunakan Metode Deep Learning - Satria Pratama, Chrisantian; Kusuma, Edward; Kristina Yanti Hutapea, Duma (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
The use of artificial intelligence is increasingly widespread, one of which is in the use of detecting an object. In general, object detection is often used in tools that capture images such as cameras on cell phones or CCTV which is applied to e-tickets (electronic tickets). With deep learning technique in this article to detect fruit, it is hoped that it can be useful in everyday life such as a fruit sorting machine based on the level of maturity based on color or separating fruit from leaves in the fruit picking process.